2015
DOI: 10.1111/jeb.12795
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of increased adult longevity in Drosophila melanogaster populations selected for adaptation to larval crowding

Abstract: In holometabolous animals such as Drosophila melanogaster, larval crowding can affect a wide range of larval and adult traits. Adults emerging from high larval density cultures have smaller body size and increased mean life span compared to flies emerging from low larval density cultures. Therefore, adaptation to larval crowding could potentially affect adult longevity as a correlated response. We addressed this issue by studying a set of large, outbred populations of D. melanogaster, experimentally evolved fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 63 publications
0
36
1
1
Order By: Relevance
“…Several studies have reported increased lifespan (e.g. Miller and Thomas, 1958;Lints and Lints, 1969;Zwaan et al, 1991;Dudas and Arking, 1995;Shenoi et al, 2016), enhanced starvation tolerance (Mueller et al, 1993), increased additive genetic variance (Imasheva and Bubliy, 2003) or elimination of fungal growth (Wertheim et al, 2002) under crowded conditions. However, some of these effects remain controversial as a result of inconsistent observations or limited experimental support (Baldal et al, 2005;Moghadam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported increased lifespan (e.g. Miller and Thomas, 1958;Lints and Lints, 1969;Zwaan et al, 1991;Dudas and Arking, 1995;Shenoi et al, 2016), enhanced starvation tolerance (Mueller et al, 1993), increased additive genetic variance (Imasheva and Bubliy, 2003) or elimination of fungal growth (Wertheim et al, 2002) under crowded conditions. However, some of these effects remain controversial as a result of inconsistent observations or limited experimental support (Baldal et al, 2005;Moghadam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on our populations show that despite their smaller body size, the MCU males have evolved higher lifespan (Shenoi et al ., ), higher courtship (Shenoi, V.N., Banerjee, S.M., Guruswamy, B., Sen, S., Ali, S.Z. & Prasad, N.G., unpublished data) and larger relative testes size (Shenoi, V.N., Negi, A., Singh, A.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies (e.g. Ribó et al ., ; Shenoi et al ., ) show that the reproductive (adult) phase of D. melanogaster can be greatly affected by the developmental (larval) phase. Larval density affects adult life‐history traits like body size (Miller & Thomas, ; Nagarajan et al ., ), fecundity (Alpatov, ; Pearl, ), lifespan (Miller & Thomas, ; Economos & Lints, ; Zwaan et al ., ) and reproductive success (Ribó et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the absence of divergence in developmental durations between the treatments was not expected, as juvenile rearing environment is predicted to have strong phenotypic effects on larval development and longevity. Typical responses to increased larval population density are prolonged developmental duration and smaller adult body weights (McNamara et al, 2010;Shenoi et al, 2016). Previous studies on P. interpunctella and the closely related almond moth, Cadra cautella, have shown that juvenile males reared at low population density had a longer juvenile developmental duration and subsequently had a longer adult lifespan (Gage, 1995;McNamara et al, 2010).…”
Section: Male Femalementioning
confidence: 99%